2022
DOI: 10.1016/j.biopha.2021.112592
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery targeted therapy in treatment of COVID-19 related ARDS. Literature review

Abstract: Introduction The most grievous complication of the COVID-19 is the acute respiratory distress syndrome. A specific, rescue treatment for rapidly deteriorating patients should emerge to improve respiratory function and help patients to survive the most challenging period. Drugs used in targeted therapy of pulmonary arterial hypertension (PAH) appears to be suitable for this task and this article describes their potential for treatment of severe cases of COVID-19. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…An additional issue is whether drugs currently used in the treatment of PH and lung fibrosis can benefit patients with PVD associated to long COVID-19. Phosphodiesterase 5 inhibitors, endothelin-1 receptor antagonists, soluble guanylyl cyclase stimulators, prostacyclin analogues, and antifibrotic drugs (pirfenidone and nintedanib) are potentially useful for long COVID-19 patients, but only small and inconclusive clinical trials have been conducted so far [ 243 , 244 ].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…An additional issue is whether drugs currently used in the treatment of PH and lung fibrosis can benefit patients with PVD associated to long COVID-19. Phosphodiesterase 5 inhibitors, endothelin-1 receptor antagonists, soluble guanylyl cyclase stimulators, prostacyclin analogues, and antifibrotic drugs (pirfenidone and nintedanib) are potentially useful for long COVID-19 patients, but only small and inconclusive clinical trials have been conducted so far [ 243 , 244 ].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…In addition, Puk et al have shown that endothelin receptor antagonists, phosphodiesterase 5 inhibitors, riociguat, and prostacyclin with its synthetic analogs could help treat COVID-19, as their beneficial effect on lungs in ARDS was reported in many studies. 42 …”
Section: Newer Aspects In the Treatment Of Pulmonary Hypertensionmentioning
confidence: 99%
“…Thus, a goal of treatment of patients hospitalized with COVID-19 should be to reduce the occurrence of PH. Drugs that were used in targeted therapy for PH prior to the pandemic, including bosentan, sildenafil and epoprostenol, have been recommended for treating patients experiencing acute respiratory distress syndrome during COVID-19 and might therefore help to achieve that goal [38]. Another treatment that has been suggested for use during COVID-19 to reduce pulmonary arterial pressure and prevent right ventricular dysfunction is inhaled nitric oxide.…”
Section: Future Investigations and Implications Of The Hypothesis Tha...mentioning
confidence: 99%